Inhibition of Antibiotic Activity In Vitro by Synthetic Melanin - Barza, Michael (1976)
Synthetic melanin (100 to 1,000 μg/ml) markedly inhibited the in vitro activity of aminoglycosides and tetracyclines but did not affect the activity of betalactam antibiotics, erythromycin, or clindamycin.